2021
DOI: 10.1016/j.psj.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exogenous phytase supplementation on phytate degradation, plasma inositol, alkaline phosphatase, and glucose concentrations of broilers at 28 days of age

Abstract: Inositol is the final product of phytate degradation, which has the potential to serve as an indicator of phytase efficacy. An experiment was conducted to evaluate effects of supplementing broiler diets with phytase on phytate degradation and plasma inositol concentrations at 28 d of age. Twenty-four Ross × Ross 708 male chicks were placed in battery cages (4 birds per cage) from 1 to 21 d of age and individually from 22 to 28 d of age. At 27 d of age, a catheter was placed in the brachial vein of broilers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Serum enzymes, such as ALP, ALT, and AST, serve as biomarkers of liver function [38]. ALP is mainly produced in the liver, kidney, and bones, and it increases inorganic phosphate levels and activates collagen fibers in the bone matrix; thus, ALP contributes to bone mineralization, as well as the functions of the liver and kidney [39,40]. In the current study, serum ALP activity decreased in broilers supplemented with a high dose of Fe-LG, which was consistent with the results reported by Yamasaki et al [41], who reported that high Fe exposure may inhibit ALP activity in osteoblastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Serum enzymes, such as ALP, ALT, and AST, serve as biomarkers of liver function [38]. ALP is mainly produced in the liver, kidney, and bones, and it increases inorganic phosphate levels and activates collagen fibers in the bone matrix; thus, ALP contributes to bone mineralization, as well as the functions of the liver and kidney [39,40]. In the current study, serum ALP activity decreased in broilers supplemented with a high dose of Fe-LG, which was consistent with the results reported by Yamasaki et al [41], who reported that high Fe exposure may inhibit ALP activity in osteoblastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Martins et al [ 53 ] observed a reduction in residual fecal phytate P of broilers fed phytase-supplemented diets (750 FTU/kg) compared to broilers fed diets with no phytase addition. Kriseldi et al [ 54 ] reported similar results when evaluating two doses of phytase (400 and 1200 FTU/kg) on phytate concentration in the ileal digesta of 28-day-old birds. The authors reported that both concentrations of phytase effectively increased phytate degradation and this led to increased inositol liberation.…”
Section: Discussionmentioning
confidence: 77%
“…In humans and animals, the gastrointestinal tract digests food and absorbs nutrients [ 1 ]. After oral administration, many Chinese herbal extracts and Chinese herbal monomers will be absorbed by the small intestine after passing through the stomach and large intestine [ 2 , 3 ]. However, intestinal absorption and bioavailability are also affected by a variety of factors (uptake, absorption time, and apparent permeation coefficient, Papp) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%